A kind of bimetallic modified lignin charcoal and its preparation method and application
Through the preparation and application of bimetal modified lignin carbon catalyst, the problems of existing catalysts being prone to carbon accumulation and low economic performance during lignin pyrolysis are solved, efficient catalytic lignin pyrolysis is achieved, bio-oil quality is improved, and waste lignin is effectively utilized.
Patent Information
- Application Number
- CN202411221414.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-02
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-09-02
AI Technical Summary
Existing catalysts are prone to carbon accumulation during the catalytic lignin pyrolysis process, and are not economically efficient, so they cannot effectively utilize the waste lignin left over from paper mills and industrial ethanol.
Bimetal modified lignin charcoal is used as a catalyst to extract lignin through industrial waste, and bimetal-supported lignin is prepared by grinding, drying, phosphoric acid treatment, ultrasonic assisted stirring and calcining, and is used as a catalyst for non-in-situ pyrolysis.
The specific surface area and mesoporous pore volume of the catalyst are improved, the catalytic activity is enhanced, the yield of aromatic hydrocarbons is promoted, the quality of bio-oil is improved, and the effective utilization of lignin resources is achieved, avoiding environmental pollution.
Smart Images

Figure CN119098174B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of preparation and application of modified catalysts, and in particular relates to a bimetallic modified lignin charcoal and a preparation method and application thereof. Background Art
[0002] The global energy crisis, fossil fuel limitations and huge environmental problems have become global challenges, accelerating the development of renewable resources and environmentally friendly alternatives to fossil fuels. Due to its abundant reserves, sustainable regeneration and carbon neutrality, lignocellulose has great potential for producing renewable liquid fuels and is expected to become a substitute for petroleum fuels, which has attracted widespread attention and attention worldwide.
[0003] Lignocellulose is composed of three major components: cellulose, hemicellulose, and lignin, and is mainly found in the cell wall skeleton of plants. Cellulose and hemicellulose have been widely used in the traditional papermaking industry. Especially with the in-depth research in recent years, the industrial production of bioethanol can be achieved with the help of effective fermentation and catalytic conversion methods. However, in these conversion methods and industrial applications, lignin is often regarded as a waste product in the utilization process, with an annual global output of nearly 50 million tons. Lignin is the most abundant aromatic biopolymer in nature, accounting for about 15-30% of the weight of lignocellulosic biomass and 40% of its energy. The calorific value of the product after pyrolysis of lignin is low and the product is complex, but high-quality bio-oil can be obtained after catalytic pyrolysis. The addition of catalysts can promote the decarbonylation, hydroxylization, and carboxylation of volatile components, remove oxygen elements in bio-oil, and convert the target product in a directional manner, and improve its selectivity and yield. Commonly used catalysts include molecular sieves, alkali metals, metal oxides, etc., but these catalysts are prone to carbon deposition and are not economical.
[0004] Biochar catalysts are inexpensive, and biochar has good porosity and specific surface area, rich functional groups and complex network structures, and has broad application prospects as carbon-based catalysts and catalyst carriers. Transition metal modification can increase the specific surface area and mesoporous pore volume of the catalyst, reduce the average pore size, and the addition of transition metals increases the active sites and acidity of the catalyst, thereby promoting demethoxylation and deoxygenation reactions through electron transfer and charge transfer interactions, increasing the yield of aromatic compounds.
[0005] Therefore, the catalytic pyrolysis of lignin by activated metal-modified lignin charcoal can increase the yield of aromatics and improve the quality of bio-oil. Summary of the invention
[0006] In order to solve the above technical problems, the present invention proposes a bimetallic modified lignin charcoal and its preparation method and application. Lignin is extracted from industrial waste to prepare bimetallic modified activated carbon, and this is used as a catalyst to catalyze the pyrolysis of lignin. In view of the current situation that the waste lignin left over from paper mills and industrial ethanol production cannot be utilized, a new type of biochar catalyst for catalytic pyrolysis of lignin is provided.
[0007] To achieve the above object, the present invention provides a method for preparing bimetallic modified lignin charcoal, comprising the following steps:
[0008] (1) grinding lignin into powder and first drying it to obtain a pretreated powder;
[0009] (2) The pretreated powder in step (1) is mixed with a phosphoric acid aqueous solution, stirred, filtered to obtain a solid, washed with deionized water until neutral, and dried to obtain pretreated lignin;
[0010] (3) dispersing the pretreated lignin described in step (2) in distilled water, adding Fe(NO3)3·9H2O and Ni(NO3)2·6H2O, and subjecting to ultrasonic-assisted stirring treatment, taking the treated solid, and performing a second drying to obtain bimetallic loaded lignin;
[0011] (4) The bimetallic loaded lignin described in step (3) is calcined in an inert atmosphere to obtain bimetallic modified lignin charcoal.
[0012] Preferably, the lignin in step (1) is enzymatically hydrolyzed lignin; the particle size of the powder in step (1) is 100 mesh; the temperature of the first drying in step (1) is 100-110° C., and the time of the first drying is 20-28 hours.
[0013] Preferably, the mixing ratio of the pretreated powder and the phosphoric acid aqueous solution in step (2) is 1g:10mL; the volume concentration of phosphoric acid in the phosphoric acid aqueous solution in step (2) is 10% to 11%; the stirring in step (2) is carried out in a water bath heating, the water bath heating temperature is 60 to 70°C, the stirring speed is 500 to 700 r / min, and the stirring time is 2 to 4h; the drying temperature in step (2) is 100 to 110°C, and the drying time is 20 to 28h.
[0014] Preferably, the amount of Fe(NO3)3·9H2O added in step (3) is calculated based on a Fe loading of 5 to 20 wt%; the amount of Ni(NO3)2·6H2O added in step (3) is calculated based on a Ni loading of 5 to 20 wt%.
[0015] Preferably, the ultrasonic power of the ultrasonic-assisted stirring treatment in step (3) is 300 W, the ultrasonic frequency is 40 KHz, the ultrasonic-assisted stirring treatment is carried out in a water bath heating, the water bath heating temperature is 60-70° C., the stirring speed is 500-700 r / min, and the stirring time is 2-4 h.
[0016] Preferably, in step (3), the temperature of the second drying is 100 to 110° C., and the time of the second drying is 12 to 18 hours.
[0017] Preferably, the inert atmosphere in step (4) is N2 atmosphere; the calcination in step (4) is to increase the temperature to 600°C at a rate of 10°C / min and calcine for 0.5 to 1.5h.
[0018] The invention also provides bimetallic modified lignin charcoal prepared by the preparation method.
[0019] The present invention also provides application of the bimetallic modified lignin carbon prepared by the preparation method in catalytic pyrolysis of lignin.
[0020] Preferably, the specific method of the application is: placing the bimetallic modified lignin charcoal and lignin in two reactors respectively in a non-in-situ manner, catalytically pyrolyzing them at 600° C. for 20 to 40 minutes in an inert atmosphere, and collecting the pyrolysis products with acetone.
[0021] Compared with the prior art, the present invention has the following advantages and technical effects:
[0022] 1. Lignin is utilized as a resource to avoid its pollution to the environment.
[0023] 2. Lignin carbon catalyst is cheaper than molecular sieve, metal oxide, alkali metal and other catalysts.
[0024] 3. For the metal-modified lignin charcoal, due to the addition of metal, the specific surface area of the catalyst is significantly increased and the number of mesopores increases.
[0025] 4. The present invention adopts non-in-situ pyrolysis, and the catalyst is not in the same reactor, which is conducive to the catalyst circulation experiment. The main components of the product are aromatic hydrocarbons, phenols, ketones, aldehydes, etc., and the yield of aromatic hydrocarbons is 10-20%. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0027] Figure 1 The figure is a flow chart of the preparation of bimetallic modified lignin charcoal of the present invention. DETAILED DESCRIPTION
[0028] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0029] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0030] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0031] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.
[0032] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0033] The enzymatic lignin used in the present invention was purchased from Shandong Longli Biotechnology Co., Ltd. In the embodiments of the present invention, if no specific conditions are specified, conventional conditions or conditions recommended by the manufacturer are used, and the raw materials, reagents, etc., whose manufacturers are not specified, are all conventional products that can be purchased commercially.
[0034] The aromatic compound content of the present invention is measured by gas chromatography-mass spectrometry (GC-MS). The percentage of the pyrolysis product in the following embodiments of the present invention is calculated as follows: w = peak area of target product / total peak area of bio-oil × 100%.
[0035] Example 1
[0036] (1) Grinding enzymatically hydrolyzed lignin into powder with a particle size of 100 mesh, and first drying at 105° C. for 24 h to obtain pretreated powder;
[0037] (2) Pretreated powder and phosphoric acid aqueous solution (phosphoric acid and water are mixed in a volume ratio of 1:7) are mixed in the ratio of 40 g: 400 mL, heated in a water bath at 60°C, stirred at a speed of 600 r / min for 3 h, filtered with a suction filter to obtain a solid, washed with deionized water until neutral, and dried at 105°C for 24 h to obtain pretreated lignin;
[0038] (3) Using the wet impregnation method, according to the carbon yield of lignin at 600°C, the mass is 42.9%, and the char yield of 10g lignin pyrolysis is 4.29g. 20wt% Fe and 5wt% Ni are loaded on 10g lignin, that is, 0.858g Fe and 0.215g Ni are required. The pretreated lignin is dispersed in distilled water, and Fe(NO3)3·9H2O and Ni(NO3)2·6H2O are added. The amount of Fe(NO3)3·9H2O added is calculated based on the Fe loading of 20wt%, and the amount of Ni(NO3)2·6H2O added is calculated based on the Ni loading of 5wt%. The ultrasonic power is 300W, the ultrasonic frequency is 40KHz, the water bath is heated at 60°C, the speed is 600r / min, and the ultrasonic-assisted stirring is treated for 3h to obtain the treated solid, and the second drying is performed at 105°C for 15h to obtain the bimetallic loaded lignin;
[0039] (4) The bimetallic loaded lignin was heated to 600 °C at a rate of 10 °C / min in a N2 atmosphere and calcined for 1 h to obtain Fe and Ni modified lignin charcoal.
[0040] Example 2
[0041] (1) Grinding enzymatically hydrolyzed lignin into powder with a particle size of 100 mesh, and first drying at 105° C. for 24 h to obtain pretreated powder;
[0042] (2) Pretreated powder and phosphoric acid aqueous solution (phosphoric acid and water are mixed in a volume ratio of 1:7) are mixed in the ratio of 40 g: 400 mL, heated in a water bath at 60°C, stirred at a speed of 600 r / min for 3 h, filtered with a suction filter to obtain a solid, washed with deionized water until neutral, and dried at 105°C for 24 h to obtain pretreated lignin;
[0043] (3) Using the wet impregnation method, according to the carbon yield of lignin at 600°C, the mass is 42.9%, and the pyrolysis carbon yield of 10g lignin is 4.29g. 5wt% Fe and 20wt% Ni are loaded on 10g lignin, that is, 0.215g Fe and 0.858g Ni are required. The pretreated lignin is dispersed in distilled water, and Fe(NO3)3·9H2O and Ni(NO3)2·6H2O are added. The amount of Fe(NO3)3·9H2O added is calculated based on the Fe loading of 5wt%, and the amount of Ni(NO3)2·6H2O added is calculated based on the Ni loading of 20wt%. The ultrasonic power is 300W, the ultrasonic frequency is 40KHz, the water bath is heated at 60°C, the speed is 600r / min, and the ultrasonic-assisted stirring is treated for 3h to obtain the treated solid, and the second drying is performed at 105°C for 15h to obtain the bimetallic loaded lignin;
[0044] (4) The bimetallic loaded lignin was heated to 600 °C at a rate of 10 °C / min in a N2 atmosphere and calcined for 1 h to obtain Fe and Ni modified lignin charcoal.
[0045] Example 3
[0046] (1) Grinding enzymatically hydrolyzed lignin into powder with a particle size of 100 mesh, and first drying at 105° C. for 24 h to obtain pretreated powder;
[0047] (2) Pretreated powder and phosphoric acid aqueous solution (phosphoric acid and water are mixed in a volume ratio of 1:7) are mixed in the ratio of 40 g: 400 mL, heated in a water bath at 60°C, stirred at a speed of 600 r / min for 3 h, filtered with a suction filter to obtain a solid, washed with deionized water until neutral, and dried at 105°C for 24 h to obtain pretreated lignin;
[0048] (3) Using the wet impregnation method, according to the carbon yield of lignin at 600°C, the mass is 42.9%, and the char yield of 10g lignin pyrolysis is 4.29g. 10wt% Fe and 15wt% Ni are loaded on 10g lignin, that is, 0.429g Fe and 0.644g Ni are required. The pretreated lignin is dispersed in distilled water, and Fe(NO3)3·9H2O and Ni(NO3)2·6H2O are added. The amount of Fe(NO3)3·9H2O added is calculated based on the Fe loading of 10wt%, and the amount of Ni(NO3)2·6H2O added is calculated based on the Ni loading of 15wt%. The ultrasonic power is 300W, the ultrasonic frequency is 40KHz, the water bath is heated at 60°C, the speed is 600r / min, and the ultrasonic-assisted stirring is treated for 3h to obtain the treated solid, and the second drying is performed at 105°C for 15h to obtain the bimetallic loaded lignin;
[0049] (4) The bimetallic loaded lignin was heated to 600 °C at a rate of 10 °C / min in a N2 atmosphere and calcined for 1 h to obtain Fe and Ni modified lignin charcoal.
[0050] Example 4
[0051] (1) Grinding enzymatically hydrolyzed lignin into powder with a particle size of 100 mesh, and first drying at 105° C. for 24 h to obtain pretreated powder;
[0052] (2) Pretreated powder and phosphoric acid aqueous solution (phosphoric acid and water are mixed in a volume ratio of 1:7) are mixed in the ratio of 40 g: 400 mL, heated in a water bath at 60°C, stirred at a speed of 600 r / min for 3 h, filtered with a suction filter to obtain a solid, washed with deionized water until neutral, and dried at 105°C for 24 h to obtain pretreated lignin;
[0053] (3) Using the wet impregnation method, according to the carbon yield of lignin at 600°C, the mass is 42.9%, and the char yield of 10g lignin pyrolysis is 4.29g. 15wt% Fe and 10wt% Ni are loaded on 10g lignin, that is, 0.644g Fe and 0.429g Ni are required. The pretreated lignin is dispersed in distilled water, and Fe(NO3)3·9H2O and Ni(NO3)2·6H2O are added. The amount of Fe(NO3)3·9H2O added is calculated based on the Fe loading of 15wt%, and the amount of Ni(NO3)2·6H2O added is calculated based on the Ni loading of 10wt%. The ultrasonic power is 300W, the ultrasonic frequency is 40KHz, the water bath is heated at 60°C, the speed is 600r / min, and the ultrasonic-assisted stirring is treated for 3h to obtain the treated solid, and the second drying is performed at 105°C for 15h to obtain the bimetallic loaded lignin;
[0054] (4) The bimetallic loaded lignin was heated to 600 °C at a rate of 10 °C / min in a N2 atmosphere and calcined for 1 h to obtain Fe and Ni modified lignin charcoal.
[0055] Comparative Example 1
[0056] (1) Grinding enzymatically hydrolyzed lignin into powder with a particle size of 100 mesh, and first drying at 105° C. for 24 h to obtain pretreated powder;
[0057] (2) Pretreated powder and phosphoric acid aqueous solution (phosphoric acid and water are mixed in a volume ratio of 1:7) are mixed in the ratio of 40 g: 400 mL, heated in a water bath at 60°C, stirred at a speed of 600 r / min for 3 h, filtered with a suction filter to obtain a solid, washed with deionized water until neutral, and dried at 105°C for 24 h to obtain pretreated lignin;
[0058] (3) The pretreated lignin was dispersed in distilled water, and the treatment was carried out for 3 h with ultrasonic power of 300 W, ultrasonic frequency of 40 KHz, water bath heating at 60 ° C, speed of 600 r / min, and ultrasonic-assisted stirring to obtain the treated solid, which was then dried for a second time at 105 ° C for 15 h;
[0059] (4) In a N2 atmosphere, the temperature was raised to 600°C at a rate of 10°C / min and calcined for 1 h to obtain modified lignin charcoal.
[0060] Comparative Example 2
[0061] (1) Grinding enzymatically hydrolyzed lignin into powder with a particle size of 100 mesh, and first drying at 105° C. for 24 h to obtain pretreated powder;
[0062] (2) Pretreated powder and phosphoric acid aqueous solution (phosphoric acid and water are mixed in a volume ratio of 1:7) are mixed in the ratio of 40 g: 400 mL, heated in a water bath at 60°C, stirred at a speed of 600 r / min for 3 h, filtered with a suction filter to obtain a solid, washed with deionized water until neutral, and dried at 105°C for 24 h to obtain pretreated lignin;
[0063] (3) Using the wet impregnation method, according to the carbon yield of lignin at 600°C, the mass is 42.9%, and the pyrolysis carbon yield of 10g lignin is 4.29g. 25wt% Fe is loaded on 10g lignin, that is, 1.073g Fe is required. The pretreated lignin is dispersed in distilled water, and Fe(NO3)3·9H2O is added. The amount of Fe(NO3)3·9H2O added is calculated based on the Fe loading of 25wt%. The ultrasonic power is 300W, the ultrasonic frequency is 40KHz, the water bath is heated at 60°C, the speed is 600r / min, and the ultrasonic-assisted stirring is treated for 3h to obtain the treated solid, which is then dried for a second time at 105°C for 15h to obtain the metal-loaded lignin;
[0064] (4) The metal-loaded lignin was heated to 600 °C at a rate of 10 °C / min in a N2 atmosphere and calcined for 1 h to obtain Fe-modified lignin charcoal.
[0065] Comparative Example 3
[0066] (1) Grinding enzymatically hydrolyzed lignin into powder with a particle size of 100 mesh, and first drying at 105° C. for 24 h to obtain pretreated powder;
[0067] (2) Pretreated powder and phosphoric acid aqueous solution (phosphoric acid and water are mixed in a volume ratio of 1:7) are mixed in the ratio of 40 g: 400 mL, heated in a water bath at 60°C, stirred at a speed of 600 r / min for 3 h, filtered with a suction filter to obtain a solid, washed with deionized water until neutral, and dried at 105°C for 24 h to obtain pretreated lignin;
[0068] (3) Using the wet impregnation method, according to the carbon yield of lignin at 600°C, the mass is 42.9%, and the pyrolysis carbon yield of 10g lignin is 4.29g. 25wt% Ni is loaded on 10g lignin, that is, 1.073gNi is required. The pretreated lignin is dispersed in distilled water, and Ni(NO3)2·6H2O is added. The amount of Ni(NO3)2·6H2O added is calculated based on the Ni loading of 25wt%. The ultrasonic power is 300W, the ultrasonic frequency is 40KHz, the water bath is heated at 60°C, the speed is 600r / min, and the ultrasonic-assisted stirring is treated for 3h to obtain the treated solid, which is then dried for a second time at 105°C for 15h to obtain the metal-loaded lignin;
[0069] (4) The metal-loaded lignin was heated to 600 °C at a rate of 10 °C / min in a N2 atmosphere and calcined for 1 h to obtain Ni-modified lignin charcoal.
[0070] Experimental Example 1
[0071] The modified lignin charcoal prepared in Examples 1 to 4 and Comparative Examples 1 to 3 was used as a catalyst and placed in two reactors with lignin, respectively. 1 g of lignin and 2 g of modified lignin charcoal were taken. Under N2 atmosphere, the heating rate was 10°C / min and the temperature reached 600°C for catalytic pyrolysis for 30 min. The oil produced during the pyrolysis process was collected and cooled and separated to obtain lignin pyrolysis oil. The distribution of the pyrolysis products was analyzed, and the results are shown in Table 1.
[0072] Table 1 Distribution of pyrolysis products
[0073]
[0074]
[0075] It can be seen from Table 1 that in Comparative Example 1, when no metal is loaded, the aromatic hydrocarbon yield is only 8.035%, and when only metal Fe and Ni are loaded in Comparative Examples 2 and 3, the aromatic hydrocarbon contents are 16.24% and 10.77%, respectively. When the Fe loading of activated carbon in Example 1 is 20wt% and the Ni loading is 5wt%, the highest aromatic hydrocarbon content is 19.075%.
[0076] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. Application of bimetallic modified lignin carbon in catalytic pyrolysis of lignin, characterized in that: The preparation method of the bimetallic modified lignin charcoal comprises the following steps: (1) Grinding lignin into powder and first drying it to obtain pretreated powder; (2) The pretreated powder in step (1) is mixed with a phosphoric acid aqueous solution, stirred, filtered to obtain a solid, washed with deionized water until neutral, and dried to obtain pretreated lignin; (3) dispersing the pretreated lignin described in step (2) in distilled water, adding Fe(NO3)3·9H2O and Ni(NO3)2·6H2O, and subjecting to ultrasonic-assisted stirring treatment, taking the treated solid, and performing a second drying to obtain bimetallic loaded lignin; (4) The bimetallic loaded lignin described in step (3) is calcined in an inert atmosphere to obtain bimetallic modified lignin charcoal.
2. The application according to claim 1, characterized in that: The lignin in step (1) is enzymatically hydrolyzed lignin; the particle size of the powder in step (1) is 100 mesh; the temperature of the first drying in step (1) is 100-110° C., and the time of the first drying is 20-28 hours.
3. The application according to claim 1, characterized in that: The mixing ratio of the pretreated powder and the phosphoric acid aqueous solution in step (2) is 1 g: 10 mL; the volume concentration of phosphoric acid in the phosphoric acid aqueous solution in step (2) is 10% to 11%; the stirring in step (2) is carried out in a water bath heating, the water bath heating temperature is 60 to 70° C., the stirring speed is 500 to 700 r / min, and the stirring time is 2 to 4 h; the drying temperature in step (2) is 100 to 110° C., and the drying time is 20 to 28 h.
4. The use according to claim 1, characterized in that: The amount of Fe(NO3)3·9H2O added in step (3) is calculated based on a Fe loading of 5 to 20 wt%; the amount of Ni(NO3)2·6H2O added in step (3) is calculated based on a Ni loading of 5 to 20 wt%.
5. The use according to claim 1, characterized in that: The ultrasonic power of the ultrasonic-assisted stirring treatment in step (3) is 300 W, the ultrasonic frequency is 40 KHz, the ultrasonic-assisted stirring treatment is carried out in a water bath heating, the water bath heating temperature is 60-70° C., the stirring speed is 500-700 r / min, and the stirring time is 2-4 h.
6. The use according to claim 1, characterized in that: In step (3), the temperature of the second drying is 100-110° C., and the time of the second drying is 12-18 hours.
7. The use according to claim 1, characterized in that: The inert atmosphere in step (4) is N2 atmosphere; the calcination in step (4) is to increase the temperature to 600°C at a rate of 10°C / min and calcine for 0.5-1.5h.
8. The use according to claim 1, characterized in that: The specific application method is: the bimetallic modified lignin charcoal and lignin are placed in two reactors respectively in a non-in-situ manner, catalytically pyrolyzed at 600° C. for 20 to 40 minutes in an inert atmosphere, and pyrolysis products are collected using acetone.
Citation Information
Patent Citations
Lignin derived carbon nickel-based multi-metal catalyst as well as preparation method and application thereof
CN115007157A